Analysis of the Influence of PSS and IPFC-POD Controllers in Small-Signal Stability Using a Simulated Annealing Algorithm - Fortes, Elenilson de Vargas; Araujo, Percival Bueno de [UNESP]; Macedo, Leonardo H. [UNESP]; Gamino, Bruno Rafael [UNESP]; Barone Martins, Luis Fabiano [UNESP]; IEEE (Ieee, 2016)
This work presents an analysis of the influence of Power System Stabilizers and the Interline Power Flow Controller-Power Oscillation Damping set in small-signal stability of electric power systems using a modified Simulated Annealing algorithm to perform a coordinated tuning of the parameters these controllers. The objective of the modified Simulated Annealing algorithm is to insert additional damping to the low frequency oscillations present in the electric power system (local and inter-area modes). In this work, the electric power system is represented by the current sensitivity model, the reason why all components and devices inserted in the system were modeled by current injection. Simulations carried out using the symmetric system of two areas allow the validation of the modified Simulated Annealing algorithm as a tool in the analysis of small signal stability, to perform a static analysis of the system, and to validate the proposed model.
Keywords: Small-signal stability; Power system stabilizers; Interline power flow controller; Power oscillation damping; Simulated Annealing